HIGH BLOOD / MILK UREA NITROGEN HAD DELETERIOUS IMPACT ON FERTILITY PARAMETERS IN CROSSBRED COWS - ANAND, I; DHALIWAL, G S; CHAWLA, P S (The Indian Journal of Animal Reproduction, 2022)
Eighty-two healthy and recently calved crossbred cows from seven dairy farms were subjected to monthly blood and milk sampling for a four-month period for blood and milk urea nitrogen (BUN/MUN) assessment. The fertility parameters like calving to first estrus interval, calving to first service interval, calving to conception interval, services per pregnancy and percent animal conceived were recorded. The cows with high BUN or MUN had similar number of days to exhibit estrus and to first service compared to their counterparts (p>0.05). The cows with low BUN or MUN had lesser number of days to conceive than those with high BUN (p<0.05) or MUN (p>0.05). The percent animals conceived followed a similar trend in both BUN and MUN groups; low level groups had higher (p<0.05) conception rates. The number of services per conception was less among cows having low BUN or MUN. In brief, high BUN/MUN have deleterious effects on fertility of lactating crossbred cows.